Nurse practitioner primary care organizational climate questionnaire: Item response theory and differential item functioning. Issue 15 (7th May 2019) - Poghosyan, Lusine; Ghaffari, Affan; Shaffer, Jonathan
Abstract: Aims and objectives: To validate Nurse Practitioner Primary Care Organizational Climate Questionnaire (NP‐PCOCQ) items using item response theory (IRT) models and conduct differential item functioning (DIF) analysis to test the item functioning among nurse practitioners (NPs) practicing in different U.S. states with variable regulations governing NP practice. Background: Nurse Practitioner Primary Care Organizational Climate Questionnaire is the only NP‐specific tool measuring NP work environment and is being used in different U.S. states with variable NP scope of practice regulations and internationally to produce evidence about NP work environments within their organisations. Design: Cross‐sectional survey design was used to collect data from 278 primary care NPs in New York (NY) and 314 NPs in Massachusetts (MA). Methods: NPs completed the 29‐item NP‐PCOCQ. Data collection involved an online survey in NY and a mail survey in MA in 2012. We used Samejima's graded response model for IRT and ordinal logistic regression for DIF analysis. A STROBE checklist was completed. Results: IRT models yielded discrimination parameters ranging from 0.98–4.65 in NY and 1.25–6.94 in MA. Item difficulty parameters were within −3 to +3 range, suggesting a fair range of item difficulties exist in the scale. Only five of the 29 items on NP‐PCOCQ exhibited DIF, suggesting some other state‐related factor besides the measured construct influenced item responses; thus, the items were removed. Conclusion: Our findings indicate that a shortened, 24‐item NP‐PCOCQ is capable of measuring organisational climate of NPs practicing in different U.S. states. NP‐PCOCQ can be used in future research to measure NP work environment. Relevance to clinical practice: The tool can also be used by practice administrators to assess NP work environment and identify deficiencies to address them. This evidence about NP work environment can be used by practice administrators to promote favourable work environments for NPs to deliver high‐quality care.